Skeletal Muscle Adaptations to Exercise Training in Young and Aged Horses - Latham, Christine M.; Owen, Randi N.; Dickson, Emily C.; Guy, Chloey P.; White-Springer, Sarah H. (Frontiers in Aging, 2021)
In aged humans, low intensity exercise increases mitochondrial density, function and oxidative capacity, decreases the prevalence of hybrid fibers, and increases lean muscle mass, but these adaptations have not been studied in aged horses. Effects of age and exercise training on muscle fiber type and size, satellite cell abundance, and mitochondrial volume density (citrate synthase activity; CS), function (cytochrome c oxidase activity; CCO), and integrative (per mg tissue) and intrinsic (per unit CS) oxidative capacities were evaluated in skeletal muscle from aged (n=9; 22±5 yr) and yearling (n=8; 9.7±0.7 mo) horses. Muscle was collected from the gluteus medius (GM) and triceps brachii at wk 0, 8, and 12 of exercise training. Data were analyzed using linear models with age, training, muscle, and all interactions as fixed effects. At wk 0, aged horses exhibited a lower percentage of type IIx (P=0.0006) and greater percentage of hybrid IIa/x fibers (P=0.002) in the GM, less satellite cells per type II fiber (P=0.03), lesser integrative and intrinsic (P≤0.04) CCO activities, lesser integrative oxidative phosphorylation capacity with complex I (PCI; P=0.02) and maximal electron transport system capacity (ECI+II; P=0.06), and greater intrinsic PCI, ECI+II, and electron transport system capacity with complex II (ECII; P≤0.05) than young horses. The percentage of type IIx fibers increased (P<0.0001) and of type IIa/x fibers decreased (P=0.001) in the GM, and the number of satellite cells per type II fiber increased (P=0.0006) in aged horses following exercise training. Conversely, the percentage of type IIa/x fibers increased (P≤0.01) and of type IIx fibers decreased (P≤0.002) in young horses. Integrative maximal oxidative capacity (P≤0.02), ECI+II (P≤0.07), and ECII (P=0.0003) increased for both age groups from wk 0 to 12. Following exercise training, aged horses had a greater percentage of IIx (P≤0.002) and lesser percentage of IIa/x fibers (P≤0.07), and more satellite cells per type II fiber (P=0.08) than young horses, but sustained lesser integrative and intrinsic CCO activities (P≤0.04) and greater intrinsic PCI, ECI+II, and ECII (P≤0.05). Exercise improved mitochondrial measures in young and aged horses; however, aged horses showed impaired mitochondrial function and differences in adaptation to exercise training.